Five Strands of Fictionality : The Institutional Construction of Contemporary American Fiction - Punday, Daniel (Book collections on Project MUSE., 2010)
"For too long, postmodernism has been described by easy generalizations--relativist, indeterminate, commercialized--that have rendered the term nearly worthless. Punday applies a more nuanced understanding of fictionality to a variety of contemporary narrative forms that occupy different locations within postmodern literary culture. Approaching postmodernism as a configuration of institutions that legitimize fictionality, he illuminates the nature of creative writing and the conflicts between different literary groups in America today"--Publisher's description.